ANALISIS KETERAMPILAN PROSES SAINS SISWA DALAM PEMBELAJARAN IPA SD - Mahmud Alpusari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2013)
This study employed a quasi-experimental method using a randomized pretest–posttest control group design. The research subjects were randomly assigned to experimental and control groups. The results revealed significant differences between classes implementing inquiry-based learning and those using conventional learning. The mean N-Gain score of students’ science process skills was highest in Primary School A, reaching 0.29, while the lowest N-Gain score was found in Primary School C at 0.15. Regarding the indicators of science process skills, the highest improvement in the experimental class was observed in the hypothesis-formulation aspect, whereas the lowest improvement occurred in the questioning aspect. In the control class, the highest indicator was also found in the hypothesis aspect, while the lowest was in the observation aspect. Overall, the science process skills of students in the experimental class demonstrated higher N-Gain values than those in the control class. These findings indicate that inquiry-based learning significantly improves students’ science process skills compared to conventional learning methods.